Evolving Evidence in Idiopathic Intracranial Hypertension - Susan P. Mollan (MDPI AG, 2021)
Idiopathic intracranial hypertension (IIH) is an enigmatic disorder characterized by raised intracranial pressure (ICP) with no known cause and it affects both children and adults [...]